PHYTOCHEMICAL, GAS CHROMATOGRAPHY-MASS SPECTROMETRY PROFILING AND FREE RADICAL SCAVENGING ACTIVITY OF EXOCARPOS LONGIFOLIUS (SANTALACEAE) EXTRACTS - Praptiwi; Fathoni, Ahmad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objectives of the study were to investigate phytochemical screening and gas chromatography-mass spectrometry (GC-MS) profiling of twigs and leaves of Exocarpos longifolius and its 2,2-diphenyl-1-picrylhydrazyl free radical scavenging activity. Methods: Phytochemical screening covering saponins, alkaloids, terpenoids, flavonoids, and tannins were carried out by standard methods. The free radical scavenging activity was performed by thin-layer chromatography - bioautography, followed by determining the IC50 values of active extracts. Chemical compounds of active extract were examined by gas chromatography/mass spectrometry. Results: The phytochemical screening revealed that all extracts have been shown to contain tannins and terpenoids, saponins were found in the methanol extract of twigs, and alkaloids were found in the ethyl acetate extracts of twigs and leaves, while flavonoids were found in the methanol extract and ethyl acetate extracts of twigs and leaves of E. longifolius. Ethyl acetate extract of twigs showed the best of IC50 value (15.65 Î¼g/mL), while ethyl acetate extract of leaves and methanol extract of twigs have strong free radical scavenging activity which IC50 were 78.59 and 67.24 Î¼g/mL, respectively. The GC-MS analysis of ethyl acetate extract of twigs has shown the presence of 12 identified compounds, and the main chemical compound is Stigmast-4-en-3-one (21.91%). Conclusions: The ethyl acetate extract of E. longifolius showed a very powerful free radical scavenging activity and revealed chemical compounds had been known to have biological activity. It might be used as a natural antioxidant.